VD_FINDINFO HC / 2012 / 261 vom 18. April 2012 - VD Tribunal cantonal (2012)
BÉNÉFICE D'INVENTAIRE, CÉDULE HYPOTHÉCAIRE, CRÉANCE | 553 CC, 319 CPC (CH), 321 al. 2 CPC (CH), 326 al. 1 CPC (CH), 104 CDPJ, 109 al. 3 CDPJ, 117 CDPJ, 118 CDPJ